A graphene oxide-assisted multi-crosslinked MXene composite film and its application
By introducing graphene oxide and cellulose into the MXene-based macrostructure, and using multiple cross-linking technology, the oxidation stability problem of MXene under H2O/O2 conditions is solved, the conductivity and mechanical properties are improved, and efficient electromagnetic shielding is achieved. and energy conversion enhances the reliability and sustainability of composite materials.
Patent Information
- Application Number
- CN202211590311.9
- Authority / Receiving Office
- CN · China
- Patent Type
- Patents(China)
- Current Assignee / Owner
- Filing Date
- 2022-12-12
- Publication Date
- 2025-01-03
- Estimated Expiration
- 2042-12-12
AI Technical Summary
The MXene-based macrostructure has poor oxidation stability under H2O/O2 conditions, resulting in poor service reliability and durability in its application. At the same time, the insulation of the polymer reduces conductivity and is difficult to prepare and process on a large scale.
The MXene composite film is used to assist multi-crosslink MXene composite film. By combining MXene with cellulose and graphene oxide, the strength of the cellulose film is enhanced by ionic liquid, and prepared by spray-assisted layer-by-layer assembly and chemical cross-linking methods to form A composite film with excellent conductivity and oxidation stability.
The composite film has high mechanical strength, hydrophobicity, water resistance, conductivity and electromagnetic shielding performance, and has photothermal/electrothermal energy conversion and antibacterial properties, which improves the reliability and sustainability of the application.
Smart Images

Figure CN116284934B_ABST
Abstract
Description
Technical Field
[0001] The present invention belongs to the technical field of composite materials, and in particular relates to a graphene oxide-assisted multi-crosslinked MXene composite film and applications thereof. Background Art
[0002] The statements herein merely provide background information related to the present invention and do not necessarily constitute prior art.
[0003] Due to the rapid development of IoT design, composite materials integrating excellent electrical conductivity, outstanding mechanical flexibility or wearable ability, durability, electromagnetic compatibility, smart heating, antibacterial properties and other multifunctional properties are the goals of the development of next-generation electronic products. Transition metal carbides or nitrides (MXene) are a new type of two-dimensional nanomaterials. Due to their excellent mechanical properties, high electrical conductivity, and abundant hydrophilic functional groups (-OH, -O, -F), they show great application potential in lightweight, flexible, high-performance electromagnetic shielding, flexible piezoresistive sensors, supercapacitors and electrodes. Despite the remarkable progress made in MXene-based macrostructures, the poor interfacial interaction between MXene sheets, poor oxidation stability under H2O / O2 conditions, and difficulty in large-scale preparation have seriously hindered their application.
[0004] Polymers are widely used as substrates or binders to improve the mechanical properties of MXene-based macrostructures. In particular, water-soluble polymers with abundant hydrophilic functional groups, such as polyvinyl alcohol, aramid nanofibers, and sodium alginate, can form strong hydrogen bonding interactions with MXenes to improve the mechanical strength and flexibility of MXene-based composites. However, the inherent insulating nature of these polymers leads to poor electrical conductivity of MXene-based composites. Although inorganic nanomaterials such as carbon nanotubes or graphene can be inserted into MXene sheets as conductive reinforcement phases to optimize the mechanical and electrical properties of MXene-based macrostructures, the complex and redundant purification and surface modification treatments of chemically inert nanocarbons are not conducive to the overall processability and scalability of the composites. Therefore, the selection of self-supporting polymers as substrates is expected to realize a separate MXene conductive layer, which helps to effectively utilize the electrical conductivity and functionality of MXenes. Nevertheless, the service reliability and durability of the above-mentioned MXene-based macrostructures are still unsatisfactory due to the poor oxidative stability of MXenes under H2O / O2 conditions. Moreover, the aforementioned polymers, as building blocks of petrochemical products, are non-renewable, which is not conducive to the construction of green and sustainable MXene-based macrostructures. Summary of the invention
[0005] In view of the shortcomings of the prior art, the object of the present invention is to provide a graphene oxide-assisted multi-cross-linked MXene composite film and its application. The graphene oxide-assisted multi-cross-linked MXene composite film provided by the present invention has good mechanical strength and toughness, hydrophobicity, water or solvent resistance and oxidation stability, while maintaining excellent conductivity and electromagnetic shielding performance, excellent photothermal / electrothermal energy conversion, photothermal antibacterial and electrothermal deicing performance, and has a broad range of applications.
[0006] In order to achieve the above object, the present invention is implemented through the following technical solutions:
[0007] In a first aspect, the present invention provides a graphene oxide-assisted multi-crosslinked MXene composite film, and the preparation method thereof is:
[0008] Methylimidazole, 2-chloroacrylonitrile and water are mixed uniformly in a mass ratio of 1-10:2-20:100-250 to prepare an ionic liquid (the function of the ionic liquid is to dissolve cellulose pulp to obtain cellulose and form ionic bonds between cellulose fibers, thereby increasing the strength of the cellulose film. The mechanical strength of the cellulose film obtained by other ionic liquids is not as high as this one);
[0009] Dissolving cellulose pulp in an ionic liquid under water bath conditions to obtain a clarified mixed solution, wherein the concentration of cellulose pulp in the mixed solution is 5-20 g / L; extruding the mixed solution into a coagulation bath for coagulation to obtain a large-area cellulose film;
[0010] The MXene aqueous dispersion was evenly sprayed on both sides of the cellulose film and dried to obtain a cellulose / MXene composite film; then the graphene oxide aqueous dispersion was evenly sprayed on both sides of the cellulose / MXene composite film and dried to obtain a cellulose / MXene / graphene oxide composite film. The amount of MXene attached to the composite film was 0.5-10 mg / cm 2 , the amount of graphene oxide attached is 0.1-2 mg / cm 2 ;
[0011] The cellulose / MXene / graphene oxide composite film is immersed in a chemical cross-linking solution to react, thereby obtaining a graphene oxide-assisted multi-cross-linked MXene composite film;
[0012] The chemical cross-linking solution is a mixed solution of a cross-linking agent, acetonitrile and methyl hexanoate, and the volume ratio of the cross-linking agent, acetonitrile and methyl hexanoate is 0.5-5:2-30:1-20.
[0013] In a second aspect, the present invention provides the application of the graphene oxide-assisted multi-crosslinked MXene composite film in the preparation of electromagnetic shielding, photothermal conversion, electrothermal conversion, thermal conductive materials, sensing materials, electrode materials, biomedical materials, antibacterial materials, supporting materials or wearable flexible electronics.
[0014] The beneficial effects achieved by one or more embodiments of the present invention are as follows:
[0015] Large-area cellulose films were prepared by a chemical solvent method, including the preparation, extrusion, molding and drying processes of cellulose / ionic liquid; the flexible cellulose films exhibited high mechanical strength due to the enhancement of hydrogen bonds and ionic bonds between cellulose chains in the ionic solution; and cellulose films with controllable thickness were obtained by easily adjusting the size of the extrusion nozzle.
[0016] The graphene oxide aqueous dispersion has excellent dispersion uniformity and stability, which is beneficial for its use as a functional ink that can be used for spraying.
[0017] Graphene oxide-assisted multi-crosslinked MXene composite films are prepared by spray-assisted layer-by-layer assembly combined with a chemical crosslinking method; MXene sheets can form strong interactions with cellulose substrates through hydrogen bonds derived from abundant hydrophilic functional groups; the sprayed MXene enables the cellulose / MXene composite film to have uniform, large-area, and orderly interconnected conductive channels, achieving excellent conductivity; an aqueous dispersion of graphene oxide is sprayed on a cellulose film to prepare a cellulose / MXene / graphene oxide composite film; large-size, high-strength graphene oxide flakes not only enhance the mechanical properties of the cellulose / MXene / graphene oxide composite film through physical crosslinking, but also improve the oxidative stability of the MXene-based composite film due to the blocking effect of graphene oxide sheets on oxygen molecules and water molecules.
[0018] The chemical cross-linking treatment endows the cellulose / MXene / graphene oxide composite film with enhanced mechanical strength and ultraflexibility caused by covalent bond interactions, including bendability, foldability, twistability, and even rollability. BRIEF DESCRIPTION OF THE DRAWINGS
[0019] The accompanying drawings in the specification, which constitute a part of the present invention, are used to provide a further understanding of the present invention. The exemplary embodiments of the present invention and their descriptions are used to explain the present invention and do not constitute improper limitations on the present invention.
[0020] Figure 1 The flexible display pictures of the graphene oxide-assisted multi-crosslinked MXene composite film provided in Example 1, wherein a is a picture of bending the composite film, b is a picture of folding the composite film in half, c is a picture of twisting the composite film, and d is a picture of winding the composite film;
[0021] Figure 2 A scanning electron microscopy image of a cross section of a graphene oxide-assisted multi-crosslinked MXene composite film provided in Example 1;
[0022] Figure 3 The water contact angle test result graph of the composite film such as graphene oxide assisted multi-crosslinked MXene provided in Example 3, wherein a is the water contact angle test graph of the composite film assisted by graphene oxide, b is the water contact angle test graph of the cellulose / MXene / graphene oxide composite film, c is the water contact angle test graph of the cellulose / MXene composite film, and d is the water contact angle test graph of the cellulose film;
[0023] Figure 4 A graph showing the test results of the water resistance of composite films such as graphene oxide-assisted multi-crosslinked MXene provided in Example 3;
[0024] Figure 5 A graph showing the stress-strain curve test results of the graphene oxide-assisted multi-crosslinked MXene and other composite films provided in Example 4;
[0025] Figure 6 A graph showing the electromagnetic shielding effectiveness test results of graphene oxide-assisted multi-crosslinked MXene composite films containing different MXene contents provided in Example 5;
[0026] Figure 7 Schematic diagram of the electromagnetic shielding mechanism of the graphene oxide-assisted multi-crosslinked MXene composite film provided in Example 5;
[0027] Figure 8 A graph showing the photothermal conversion effect test results of the graphene oxide-assisted multi-crosslinked MXene composite film provided in Example 6;
[0028] Fig. 9 This is a graph showing the test results of the electrothermal conversion effect of the graphene oxide-assisted multi-cross-linked MXene composite film provided in Example 6. DETAILED DESCRIPTION
[0029] It should be noted that the following detailed descriptions are illustrative and intended to provide further explanation of the present invention. Unless otherwise specified, all technical and scientific terms used in the present invention have the same meanings as those commonly understood by those skilled in the art to which the present invention belongs.
[0030] In a first aspect, the present invention provides a graphene oxide-assisted multi-crosslinked MXene composite film, and the preparation method thereof is:
[0031] Methylimidazole, 2-chloroacrylonitrile and water are mixed uniformly in a mass ratio of 1-10:2-20:100-250 to prepare an ionic liquid; the ionic liquid dissolves cellulose pulp to obtain cellulose and forms ionic bonds between cellulose fibers, thereby increasing the strength of the cellulose film. The mechanical strength of the cellulose film obtained by other ionic liquids is not as high as this one.
[0032] Dissolving cellulose pulp in an ionic liquid under water bath conditions to obtain a clarified mixed solution, wherein the concentration of cellulose pulp in the mixed solution is 5-20 g / L; extruding the mixed solution into a coagulation bath for coagulation to obtain a large-area cellulose film;
[0033] The MXene aqueous dispersion was evenly sprayed on both sides of the cellulose film and dried to obtain a cellulose / MXene composite film; then the graphene oxide aqueous dispersion was evenly sprayed on both sides of the cellulose / MXene composite film and dried to obtain a cellulose / MXene / graphene oxide composite film. The amount of MXene attached to the composite film was 0.5-10 mg / cm 2 , the amount of graphene oxide attached is 0.1-2 mg / cm 2 ;
[0034] The cellulose / MXene / graphene oxide composite film is immersed in a chemical cross-linking solution to react, thereby obtaining a graphene oxide-assisted multi-cross-linked MXene composite film;
[0035] The chemical cross-linking solution is a mixed solution of a cross-linking agent, acetonitrile and methyl hexanoate, and the volume ratio of the cross-linking agent, acetonitrile and methyl hexanoate is 0.5-5:2-30:1-20.
[0036] Large-area cellulose films were prepared by a chemical solvent method, including the preparation, extrusion, molding and drying processes of cellulose / ionic liquid; the flexible cellulose films exhibited high mechanical strength due to the enhancement of hydrogen bonds and ionic bonds between cellulose chains in the ionic solution; and cellulose films with controllable thickness were obtained by easily adjusting the size of the extrusion nozzle.
[0037] The graphene oxide aqueous dispersion has excellent dispersion uniformity and stability, which is beneficial for its use as a functional ink that can be used for spraying.
[0038] Graphene oxide-assisted multi-crosslinked MXene composite films are prepared by spray-assisted layer-by-layer assembly combined with a chemical crosslinking method; MXene sheets can form strong interactions with cellulose substrates through hydrogen bonds derived from abundant hydrophilic functional groups; the sprayed MXene enables the cellulose / MXene composite film to have uniform, large-area, and orderly interconnected conductive channels, achieving excellent conductivity; an aqueous dispersion of graphene oxide is sprayed on a cellulose film to prepare a cellulose / MXene / graphene oxide composite film; large-size, high-strength graphene oxide flakes not only enhance the mechanical properties of the cellulose / MXene / graphene oxide composite film through physical crosslinking, but also improve the oxidative stability of the MXene-based composite film due to the blocking effect of graphene oxide sheets on oxygen molecules and water molecules.
[0039] The chemical cross-linking treatment endows the cellulose / MXene / graphene oxide composite film with enhanced mechanical strength and ultraflexibility caused by covalent bond interactions, including bendability, foldability, twistability, and even rollability.
[0040] In some embodiments, the water bath conditions are as follows: the water bath heating temperature is 55-125° C., and the water bath heating time is 0.2-2.5 h, so as to accelerate the dissolution of cellulose pulp.
[0041] In some embodiments, the mixed liquid is extruded into the coagulation bath using an extrusion nozzle, and the width of the extrusion nozzle is selected from 1.65mm, 1.55mm, 1.36mm, 1.2mm, 1.12mm, 0.84mm, 0.7mm, 0.6mm, 0.51mm, 0.41mm, 0.34mm, 0.3mm, 0.26mm, 0.24mm, 0.21mm, 0.16mm, 0.11mm or 0.06mm, preferably 0.3mm.
[0042] The coagulation bath is selected from ethanol, isopropanol or acetic acid, or a mixture of two of them.
[0043] In some embodiments, the preparation method of the MXene aqueous dispersion is: adding Ti3AlC2MAX powder to a mixed solution of LiF and concentrated hydrochloric acid in batches for etching, washing, shaking and layering after etching, adding the obtained MXene to water and dispersing it evenly to obtain an MXene aqueous dispersion;
[0044] The shaking layering treatment is hand shaking or ultrasonic treatment, so that the multi-layer MXene is peeled off to obtain a single-layer MXene;
[0045] In the mixed solution of LiF and concentrated hydrochloric acid, the mass ratio of LiF to concentrated hydrochloric acid is 3-6:40-60, and the concentration of concentrated hydrochloric acid is 5-8 mol / L, preferably 5-7 mol / L, such as 6 mol / L.
[0046] The Ti3AlC2MAX powder has a dense rock morphology.
[0047] Preferably, the time for adding Ti3AlC2MAX powder in batches is 20-30 minutes. The purpose of adding Ti3AlC2MAX powder in batches is to increase the dispersibility of Ti3AlC2 MAX powder and improve etching efficiency. The present invention has no special requirements for the conditions of the magnetic stirring, and the magnetic stirring conditions well known in the art can be used.
[0048] Preferably, the etching temperature is 33-40° C., and the etching time is 20-30 h.
[0049] The reaction product after etching is preferably transferred to a centrifuge tube, diluted and washed with an appropriate amount of deionized water, and then centrifuged at 4000rpm in a centrifuge for 5 minutes, and the solid precipitate is dispersed by adding deionized water again, and the centrifugation operation is repeated until the pH value is about 7; then the solid precipitate is dispersed in water and subjected to a shaking layering treatment for 10-60 minutes. Then, the reaction product after the shaking layering treatment is preferably transferred to a centrifuge tube, and then centrifuged at 3500rpm in a centrifuge for 10 minutes; the supernatant is the MXene dispersion.
[0050] In some embodiments, the preparation method of the graphene oxide aqueous dispersion is: dissolving sodium nitrate in concentrated sulfuric acid to obtain a uniform and clear mixed solution;
[0051] Add graphite powder to the uniform clear mixed solution, cool it in an ice water bath, slowly add potassium permanganate under stirring, stir and react for 5-15 minutes, turn off the agitator, add deionized water to the reaction solution, wait until the temperature of the mixed solution is 65-75° C., add hydrogen peroxide, stir and react for 8-12 hours to obtain a product, wash the product, and evenly disperse it in water to obtain an aqueous dispersion of graphene oxide;
[0052] Wherein, the mass ratio of the sodium nitrate, concentrated sulfuric acid, graphite powder, potassium permanganate, deionized water and hydrogen peroxide is 0.2-5.0:100-500:0.5-10:10-60:50-500:5-50.
[0053] Concentrated sulfuric acid acts as a strong proton acid and enters the graphite interlayer; potassium permanganate acts as a strong oxidant to generate graphite oxide, and graphene oxide is obtained through ultrasonic exfoliation. In a strong acid environment, the nitrate ion of sodium nitrate has strong oxidizing properties; the role of hydrogen peroxide is to remove excess potassium permanganate in the oxidation, oxidizing it into divalent manganese ions and removing it. The reaction is exothermic, so the temperature needs to be lowered to 10°C to prevent the danger of violent exotherm.
[0054] In some embodiments, the crosslinking agent is selected from one or a combination of at least two of hexamethylene diisocyanate, methylene diphenyl isocyanate, polymethylene polyphenyl isocyanate, toluene diisocyanate or isophorone diisocyanate.
[0055] Preferably, the temperature for chemical cross-linking of the cellulose / MXene / graphene oxide composite film is 65-75° C., and the time for chemical cross-linking is 1.5-2.5 h.
[0056] Preferably, when the cellulose / MXene / graphene oxide composite film is chemically cross-linked, the reaction container is sealed to prevent the volatilization of the cross-linking solvent.
[0057] In some embodiments, the concentration of the MXene aqueous dispersion is 0.05-1 wt %.
[0058] In some embodiments, the concentration of the graphene oxide aqueous dispersion is 0.5-2 wt %.
[0059] In a second aspect, the present invention provides the application of the graphene oxide-assisted multi-crosslinked MXene composite film in the preparation of electromagnetic shielding, photothermal conversion, electrothermal conversion, thermal conductive materials, sensing materials, electrode materials, biomedical materials, antibacterial materials, supporting materials or wearable flexible electronics.
[0060] The graphene oxide-assisted multi-cross-linked MXene composite film provided by the present invention and its preparation method and application are described in detail below in conjunction with the embodiments, but they should not be understood as limiting the scope of protection of the present invention.
[0061] Example 1
[0062] 4.0 parts by mass of methylimidazole and 12.0 parts by mass of 2-chloroacrylonitrile are added to 100 parts by mass of deionized water, and stirred continuously until dissolved to obtain a uniform ionic liquid; cellulose pulp is added to the above ionic liquid, and stirred continuously for 0.5 hours under 90°C water bath conditions until dissolved to obtain a uniform and clear cellulose / ionic liquid; the above cellulose / ionic liquid is extruded into a water coagulation bath through an extrusion nozzle with a width of 0.11 mm and coagulated for 30 minutes; the cellulose film in the above coagulation bath is taken out, washed with deionized water and dried naturally in air at room temperature to obtain a large-area cellulose film.
[0063] Slowly add 5.0 parts by mass of LiF to the polytetrafluoroethylene reactor liner containing 50.0 parts by mass of concentrated hydrochloric acid to dissolve and stir evenly to obtain an etching solution; add 3.2 parts by mass of Ti3AlC2 MAX powder to the above etching solution in portions within 20 to 30 minutes; then seal the polytetrafluoroethylene reactor liner and place it in a 35°C constant temperature water bath for continuous stirring for 24 hours. Then, transfer the reaction product after the above etching to a centrifuge tube, add an appropriate amount of deionized water to dilute and wash, then centrifuge at 4000rpm in a centrifuge for 5 minutes, take the solid precipitate and add deionized water to disperse it again, repeat the centrifugation operation until the pH value is about 7; then disperse the solid precipitate in water, perform oscillation and stratification treatment, and the oscillation time is 30 minutes to obtain a single-layer MXene sheet dispersion; finally, add deionized water to the MXene sheet dispersion and mix and disperse evenly to obtain a MXene aqueous dispersion with a concentration of 1wt%.
[0064] The aqueous dispersion of graphene oxide is prepared by an improved Hummer's method: 5.0 parts by mass of sodium nitrate is dissolved in 300 parts by mass of concentrated sulfuric acid to obtain a uniform clear mixed solution; then 3.0 parts by mass of graphite powder is added to the mixed solution, and after the solution temperature is reduced to 10°C in an ice-water bath, 15 parts by mass of potassium permanganate is slowly added and continuously stirred; after stirring for 10 minutes, the agitator is turned off, 300 parts by mass of deionized water are poured into the beaker to obtain a mixed solution, and after the mixed solution is cooled to 70°C, 30 parts by mass of hydrogen peroxide is added and stirred overnight; finally, after several deionized water washings and centrifugal treatments, the mixture is added into deionized water and dispersed uniformly to obtain the aqueous dispersion of graphene oxide.
[0065] The above-mentioned MXene aqueous dispersion is evenly sprayed on the surface of the cellulose film by a spraying equipment, and then the above-mentioned cellulose / MXene composite film is placed in a 50°C oven for drying; the above-mentioned step is repeated twice on the other side of the cellulose film, and the mass change of the cellulose / MXene composite film is recorded; the graphene oxide aqueous dispersion is evenly sprayed on both sides of the cellulose / MXene composite film and dried to obtain a cellulose / MXene / graphene oxide composite film.
[0066] 6 parts by mass of polymethylene polyphenyl isocyanate, 48 parts by mass of acetonitrile and 16 parts by mass of methyl hexanoate were added to a beaker and stirred evenly by magnetic force to obtain a chemical crosslinking solution. The intermediate product of cellulose / MXene / graphene oxide composite film was immersed in a beaker containing the above chemical crosslinking solution and the beaker was sealed with a sealing film; then the beaker was placed in an oven at a temperature of 70°C and reacted for 2 hours. Finally, the cellulose / MXene / graphene oxide composite film was taken out with tweezers and rinsed with acetone 2-3 times to effectively remove the excess chemical crosslinking solution attached to the surface. The washed cellulose / MXene / graphene oxide composite film was placed in an oven at 50°C and dried for 8 hours to obtain a graphene oxide-assisted multi-crosslinked MXene composite film.
[0067] The graphene oxide-assisted multi-crosslinked MXene composite film exhibits flexibility such as Figure 1 shown.
[0068] The scanning electron microscopy image of the cross section of the graphene oxide-assisted multi-crosslinked MXene composite film is shown in FIG. Figure 2 As shown, from the innermost layer to the outermost layer, they are cellulose film, MXene sheet, and graphene oxide sheet.
[0069] Example 2
[0070] 2.0 parts by mass of methylimidazole and 10.0 parts by mass of 2-chloroacrylonitrile are added to 120 parts by mass of deionized water, and stirred continuously until dissolved to obtain a uniform ionic liquid; cellulose pulp is added to the above ionic liquid, and stirred continuously for 0.5 hours in a 90°C water bath condition until dissolved to obtain a uniform and clear cellulose / ionic liquid; the above cellulose / ionic liquid is extruded into a water coagulation bath through an extrusion nozzle with a width of 0.3 mm and coagulated for 30 minutes; the cellulose film in the above coagulation bath is taken out, washed with deionized water and dried naturally in air at room temperature to obtain a large-area cellulose film.
[0071] Slowly add 5.0 parts by mass of LiF to the polytetrafluoroethylene reactor liner containing 50.0 parts by mass of concentrated hydrochloric acid to dissolve and stir evenly to obtain an etching solution; add 3.2 parts by mass of Ti3AlC2 MAX powder to the above etching solution in portions within 20 to 30 minutes; then seal the polytetrafluoroethylene reactor liner and place it in a 35°C constant temperature water bath for continuous stirring for 24 hours. Then, transfer the reaction product after the above etching to a centrifuge tube, add an appropriate amount of deionized water to dilute and wash, then centrifuge at 4000rpm in a centrifuge for 5 minutes, take the solid precipitate and add deionized water to disperse it again, repeat the centrifugation operation until the pH value is about 7; then disperse the solid precipitate in water, perform oscillation and stratification treatment, and the oscillation time is 30 minutes to obtain a single-layer MXene sheet dispersion; finally, add deionized water to the MXene sheet dispersion and mix and disperse evenly to obtain a MXene aqueous dispersion with a concentration of 1wt%.
[0072] The aqueous dispersion of graphene oxide is prepared by an improved Hummer's method: 1.0 parts by mass of sodium nitrate is dissolved in 200 parts by mass of concentrated sulfuric acid to obtain a uniform and clear mixed solution; then 2.0 parts by mass of graphite powder is added to the mixed solution, and after the solution temperature is reduced to 10°C in an ice-water bath, 20 parts by mass of potassium permanganate is slowly added and continuously stirred; after stirring for 10 minutes, the agitator is turned off, 300 parts by mass of deionized water are poured into the beaker to obtain a mixed solution, and after the mixed solution is cooled to 70°C, 30 parts by mass of hydrogen peroxide is added and stirred overnight; finally, after washing with deionized water several times and centrifuging, the mixture is added into deionized water and dispersed uniformly to obtain the aqueous dispersion of graphene oxide.
[0073] The above-mentioned MXene aqueous dispersion is evenly sprayed on the surface of the cellulose film by a spraying equipment, and then the above-mentioned cellulose / MXene composite film is placed in a 50°C oven for drying; the above-mentioned step is repeated 5 times on the other side of the cellulose film, and the mass change of the cellulose / MXene composite film is recorded; the graphene oxide aqueous dispersion is evenly sprayed on both sides of the cellulose / MXene composite film and dried to obtain a cellulose / MXene / graphene oxide composite film.
[0074] 6 parts by mass of polymethylene polyphenyl isocyanate, 48 parts by mass of acetonitrile and 16 parts by mass of methyl hexanoate were added to a beaker and stirred evenly by magnetic force to obtain a chemical crosslinking solution. The intermediate product of cellulose / MXene / graphene oxide composite film was immersed in a beaker containing the above chemical crosslinking solution and the beaker was sealed with a sealing film; then the beaker was placed in an oven at a temperature of 70°C and reacted for 2 hours. Finally, the cellulose / MXene / graphene oxide composite film was taken out with tweezers and rinsed with acetone 2-3 times to effectively remove the excess chemical crosslinking solution attached to the surface. The washed cellulose / MXene / graphene oxide composite film was placed in an oven at 50°C and dried for 8 hours to obtain a graphene oxide-assisted multi-crosslinked MXene composite film.
[0075] Example 3
[0076] 8.0 parts by mass of methylimidazole and 18.0 parts by mass of 2-chloroacrylonitrile are added to 120 parts by mass of deionized water, and stirred continuously until dissolved to obtain a uniform ionic liquid; cellulose pulp is added to the above ionic liquid, and stirred continuously for 2 hours under 90°C water bath conditions until dissolved to obtain a uniform and clear cellulose / ionic liquid; the above cellulose / ionic liquid is extruded into a water coagulation bath through an extrusion nozzle with a width of 1.65 mm and coagulated for 60 minutes; the cellulose film in the above coagulation bath is taken out, washed with deionized water and dried naturally at room temperature in air to obtain a large-area cellulose film.
[0077] Slowly add 5.0 parts by mass of LiF to the polytetrafluoroethylene reactor liner containing 50.0 parts by mass of concentrated hydrochloric acid to dissolve and stir evenly to obtain an etching solution; add 3.2 parts by mass of Ti3AlC2 MAX powder to the above etching solution in portions within 20 to 30 minutes; then seal the polytetrafluoroethylene reactor liner and place it in a 35°C constant temperature water bath for continuous stirring for 24 hours. Then, transfer the reaction product after the above etching to a centrifuge tube, add an appropriate amount of deionized water to dilute and wash, then centrifuge at 4000rpm in a centrifuge for 5 minutes, take the solid precipitate and add deionized water to disperse it again, repeat the centrifugation operation until the pH value is about 7; then disperse the solid precipitate in water, perform oscillation and stratification treatment, and the oscillation time is 30 minutes to obtain a single-layer MXene sheet dispersion; finally, add deionized water to the MXene sheet dispersion and mix and disperse evenly to obtain a MXene aqueous dispersion with a concentration of 1wt%.
[0078] The aqueous dispersion of graphene oxide is prepared by an improved Hummer's method: 1.0 parts by mass of sodium nitrate is dissolved in 200 parts by mass of concentrated sulfuric acid to obtain a uniform and clear mixed solution; then 2.0 parts by mass of graphite powder is added to the mixed solution, and after the solution temperature is reduced to 10°C in an ice-water bath, 20 parts by mass of potassium permanganate is slowly added and continuously stirred; after stirring for 10 minutes, the agitator is turned off, 300 parts by mass of deionized water are poured into the beaker to obtain a mixed solution, and after the mixed solution is cooled to 70°C, 30 parts by mass of hydrogen peroxide is added and stirred overnight; finally, after washing with deionized water several times and centrifuging, the mixture is added into deionized water and dispersed uniformly to obtain the aqueous dispersion of graphene oxide.
[0079] The above-mentioned MXene aqueous dispersion is evenly sprayed on the surface of the cellulose film by a spraying equipment, and then the above-mentioned cellulose / MXene composite film is placed in a 50°C oven for drying; the above-mentioned step is repeated 8 times on the other side of the cellulose film, and the mass change of the cellulose / MXene composite film is recorded; the graphene oxide aqueous dispersion is evenly sprayed on both sides of the cellulose / MXene composite film and dried to obtain a cellulose / MXene / graphene oxide composite film.
[0080] 6 parts by mass of hexamethylene diisocyanate, 48 parts by mass of acetonitrile and 16 parts by mass of methyl hexanoate were added to a beaker and stirred evenly by magnetic force to obtain a chemical crosslinking solution. The intermediate product of cellulose / MXene / graphene oxide composite film was immersed in a beaker containing the above chemical crosslinking solution and the beaker was sealed with a sealing film; then the beaker was placed in an oven at a temperature of 70°C and reacted for 2 hours. Finally, the cellulose / MXene / graphene oxide composite film was taken out with tweezers and rinsed with acetone 2-3 times to effectively remove the excess chemical crosslinking solution attached to the surface. The washed cellulose / MXene / graphene oxide composite film was placed in a 50°C oven and dried for 8 hours to obtain a graphene oxide-assisted multi-crosslinked MXene composite film.
[0081] The water contact angle and water resistance test results of the graphene oxide-assisted multi-crosslinked MXene composite film are shown in Figures 1 and 2. Figure 3 and Figure 4 As shown by Figure 3 It can be seen that the water contact angle of graphene oxide-assisted multi-cross-linked MXene composite film is 105°, which is significantly larger than the water contact angles of cellulose / MXene / graphene oxide composite film, cellulose / MXene composite film and cellulose film, indicating that it has better hydrophobicity.
[0082] Depend on Figure 4It can be seen that the graphene oxide-assisted multi-crosslinked MXene composite film, cellulose / MXene / graphene oxide composite film and cellulose / MXene composite film were placed in water and ultrasonically treated for 30 minutes. The graphene oxide-assisted multi-crosslinked MXene composite film can float on the water surface and remain intact, while the cellulose / MXene / graphene oxide composite film is partially decomposed and the cellulose / MXene composite film is completely decomposed, indicating that the graphene oxide-assisted multi-crosslinked MXene composite film has better waterproofness.
[0083] Example 4
[0084] 10.0 parts by mass of methylimidazole and 20.0 parts by mass of 2-chloroacrylonitrile are added to 250 parts by mass of deionized water, and stirred continuously until dissolved to obtain a uniform ionic liquid; cellulose pulp is added to the above ionic liquid, and stirred continuously for 0.5 hours under 90°C water bath conditions until dissolved to obtain a uniform and clear cellulose / ionic liquid; the above cellulose / ionic liquid is extruded into a water coagulation bath through an extrusion nozzle with a width of 0.3 mm and coagulated for 30 minutes; the cellulose film in the above coagulation bath is taken out, washed with deionized water and dried naturally at room temperature in air to obtain a large-area cellulose film.
[0085] Slowly add 5.0 parts by mass of LiF to the polytetrafluoroethylene reactor liner containing 50.0 parts by mass of concentrated hydrochloric acid to dissolve and stir evenly to obtain an etching solution; add 3.2 parts by mass of Ti3AlC2 MAX powder to the above etching solution in portions within 20 to 30 minutes; then seal the polytetrafluoroethylene reactor liner and place it in a 35°C constant temperature water bath for continuous stirring for 24 hours. Then, transfer the reaction product after the above etching to a centrifuge tube, add an appropriate amount of deionized water to dilute and wash, then centrifuge at 4000rpm in a centrifuge for 5 minutes, take the solid precipitate and add deionized water to disperse it again, repeat the centrifugation operation until the pH value is about 7; then disperse the solid precipitate in water, perform oscillation and stratification treatment, and the oscillation time is 30 minutes to obtain a single-layer MXene sheet dispersion; finally, add deionized water to the MXene sheet dispersion and mix and disperse evenly to obtain a MXene aqueous dispersion with a concentration of 1wt%.
[0086] The aqueous dispersion of graphene oxide is prepared by an improved Hummer's method: 1.0 parts by mass of sodium nitrate is dissolved in 200 parts by mass of concentrated sulfuric acid to obtain a uniform and clear mixed solution; then 2.0 parts by mass of graphite powder is added to the mixed solution, and after the solution temperature is reduced to 10°C in an ice-water bath, 20 parts by mass of potassium permanganate is slowly added and continuously stirred; after stirring for 10 minutes, the agitator is turned off, 300 parts by mass of deionized water are poured into the beaker to obtain a mixed solution, and after the mixed solution is cooled to 70°C, 30 parts by mass of hydrogen peroxide is added and stirred overnight; finally, after washing with deionized water several times and centrifuging, the mixture is added into deionized water and dispersed uniformly to obtain the aqueous dispersion of graphene oxide.
[0087] The above-mentioned MXene aqueous dispersion is evenly sprayed on the surface of the cellulose film by a spraying equipment, and then the above-mentioned cellulose / MXene composite film is placed in a 50°C oven for drying; the above-mentioned step is repeated 11 times on the other side of the cellulose film, and the mass change of the cellulose / MXene composite film is recorded; the graphene oxide aqueous dispersion is evenly sprayed on both sides of the cellulose / MXene composite film and dried to obtain a cellulose / MXene / graphene oxide composite film.
[0088] 8 parts by mass of phenyl methylene diisocyanate, 40 parts by mass of acetonitrile and 18 parts by mass of methyl hexanoate were added to a beaker and stirred evenly by magnetic force to obtain a chemical crosslinking solution. The intermediate product of cellulose / MXene / graphene oxide composite film was immersed in a beaker containing the above chemical crosslinking solution and the beaker was sealed with a sealing film; then the beaker was placed in an oven at a temperature of 70°C and reacted for 2 hours. Finally, the cellulose / MXene / graphene oxide composite film was taken out with tweezers and rinsed with acetone 2-3 times to effectively remove the excess chemical crosslinking solution attached to the surface. The washed cellulose / MXene / graphene oxide composite film was placed in an oven at 50°C and dried for 8 hours to obtain a graphene oxide-assisted multi-crosslinked MXene composite film.
[0089] The stress-strain curve test results of the graphene oxide-assisted multi-crosslinked MXene composite film are shown in the figure below: Figure 5 As shown, the tensile strength of the graphene oxide-assisted multi-cross-linked MXene composite film can reach 324 MPa.
[0090] Example 5
[0091] 8.0 parts by mass of methylimidazole and 10.0 parts by mass of 2-chloroacrylonitrile are added to 200 parts by mass of deionized water, and stirred continuously until dissolved to obtain a uniform ionic liquid; cellulose pulp is added to the above ionic liquid, and stirred continuously for 0.5 hours under 90°C water bath conditions until dissolved to obtain a uniform and clear cellulose / ionic liquid; the above cellulose / ionic liquid is extruded into a water coagulation bath through an extrusion nozzle with a width of 0.84 mm and coagulated for 30 minutes; the cellulose film in the above coagulation bath is taken out, washed with deionized water and dried naturally at room temperature in air to obtain a large-area cellulose film.
[0092] Slowly add 5.0 parts by mass of LiF to the polytetrafluoroethylene reactor liner containing 50.0 parts by mass of concentrated hydrochloric acid to dissolve and stir evenly to obtain an etching solution; add 3.2 parts by mass of Ti3AlC2 MAX powder to the above etching solution in portions within 20 to 30 minutes; then seal the polytetrafluoroethylene reactor liner and place it in a 35°C constant temperature water bath for continuous stirring for 24 hours. Then, transfer the reaction product after the above etching to a centrifuge tube, add an appropriate amount of deionized water to dilute and wash, then centrifuge at 4000rpm in a centrifuge for 5 minutes, take the solid precipitate and add deionized water to disperse it again, repeat the centrifugation operation until the pH value is about 7; then disperse the solid precipitate in water, perform oscillation and stratification treatment, and the oscillation time is 30 minutes to obtain a single-layer MXene sheet dispersion; finally, add deionized water to the MXene sheet dispersion and mix and disperse evenly to obtain a MXene aqueous dispersion with a concentration of 1wt%.
[0093] The aqueous dispersion of graphene oxide is prepared by an improved Hummer's method: 1.0 parts by mass of sodium nitrate is dissolved in 200 parts by mass of concentrated sulfuric acid to obtain a uniform and clear mixed solution; then 2.0 parts by mass of graphite powder is added to the mixed solution, and after the solution temperature is reduced to 10°C in an ice-water bath, 20 parts by mass of potassium permanganate is slowly added and continuously stirred; after stirring for 10 minutes, the agitator is turned off, 300 parts by mass of deionized water are poured into the beaker to obtain a mixed solution, and after the mixed solution is cooled to 70°C, 30 parts by mass of hydrogen peroxide is added and stirred overnight; finally, after washing with deionized water several times and centrifuging, the mixture is added into deionized water and dispersed uniformly to obtain the aqueous dispersion of graphene oxide.
[0094] The above-mentioned MXene aqueous dispersion is evenly sprayed on the surface of the cellulose film by a spraying equipment, and then the above-mentioned cellulose / MXene composite film is placed in a 50°C oven for drying; the above-mentioned step is repeated 14 times on the other side of the cellulose film, and the mass change of the cellulose / MXene composite film is recorded; the graphene oxide aqueous dispersion is evenly sprayed on both sides of the cellulose / MXene composite film and dried to obtain a cellulose / MXene / graphene oxide composite film.
[0095] 8 parts by mass of polymethylene polyphenyl isocyanate, 40 parts by mass of acetonitrile and 15 parts by mass of methyl hexanoate were added to a beaker and stirred evenly by magnetic force to obtain a chemical crosslinking solution. The intermediate product of cellulose / MXene / graphene oxide composite film was immersed in a beaker containing the above chemical crosslinking solution and the beaker was sealed with a sealing film; then the beaker was placed in an oven at a temperature of 70°C and reacted for 2 hours. Finally, the cellulose / MXene / graphene oxide composite film was taken out with tweezers and rinsed with acetone 2-3 times to effectively remove the excess chemical crosslinking solution attached to the surface. The washed cellulose / MXene / graphene oxide composite film was placed in an oven at 50°C and dried for 8 hours to obtain a graphene oxide-assisted multi-crosslinked MXene composite film.
[0096] The electromagnetic shielding effectiveness test results and electromagnetic shielding mechanism schematic diagram of the graphene oxide assisted multi-crosslinked MXene composite film are shown in Figure 6 and Figure 7 By controlling the number of times of repeating the MXene spraying step, graphene oxide-assisted multi-crosslinked MXene composite films with MXene mass fractions of 15wt%, 32wt%, 52wt%, 71wt% and 95wt% were obtained, and the corresponding electromagnetic shielding effectiveness were 21dB, 37dB, 54dB, 64dB and 71dB, respectively.
[0097] Example 6
[0098] 3.0 parts by mass of methylimidazole and 5.0 parts by mass of 2-chloroacrylonitrile are added to 100 parts by mass of deionized water, and stirred continuously until dissolved to obtain a uniform ionic liquid; cellulose pulp is added to the above ionic liquid, and stirred continuously for 0.5 hours under 90°C water bath conditions until dissolved to obtain a uniform and clear cellulose / ionic liquid; the above cellulose / ionic liquid is extruded into a water coagulation bath through an extrusion nozzle with a width of 0.06 mm and coagulated for 30 minutes; the cellulose film in the above coagulation bath is taken out, washed with deionized water and dried naturally at room temperature in air to obtain a large-area cellulose film.
[0099] Slowly add 5.0 parts by mass of LiF to the polytetrafluoroethylene reactor liner containing 50.0 parts by mass of concentrated hydrochloric acid to dissolve and stir evenly to obtain an etching solution; add 3.2 parts by mass of Ti3AlC2 MAX powder to the above etching solution in portions within 20 to 30 minutes; then seal the polytetrafluoroethylene reactor liner and place it in a 35°C constant temperature water bath for continuous stirring for 24 hours. Then, transfer the reaction product after the above etching to a centrifuge tube, add an appropriate amount of deionized water to dilute and wash, then centrifuge at 4000rpm in a centrifuge for 5 minutes, take the solid precipitate and add deionized water to disperse it again, repeat the centrifugation operation until the pH value is about 7; then disperse the solid precipitate in water, perform oscillation and stratification treatment, and the oscillation time is 30 minutes to obtain a single-layer MXene sheet dispersion; finally, add deionized water to the MXene sheet dispersion and mix and disperse evenly to obtain a MXene aqueous dispersion with a concentration of 1wt%.
[0100] The aqueous dispersion of graphene oxide is prepared by an improved Hummer's method: 1.0 parts by mass of sodium nitrate is dissolved in 200 parts by mass of concentrated sulfuric acid to obtain a uniform and clear mixed solution; then 2.0 parts by mass of graphite powder is added to the mixed solution, and after the solution temperature is reduced to 10°C in an ice-water bath, 20 parts by mass of potassium permanganate is slowly added and continuously stirred; after stirring for 10 minutes, the agitator is turned off, 300 parts by mass of deionized water are poured into the beaker to obtain a mixed solution, and after the mixed solution is cooled to 70°C, 30 parts by mass of hydrogen peroxide is added and stirred overnight; finally, after washing with deionized water several times and centrifuging, the mixture is added into deionized water and dispersed uniformly to obtain the aqueous dispersion of graphene oxide.
[0101] The above-mentioned MXene aqueous dispersion is evenly sprayed on the surface of the cellulose film by a spraying equipment, and then the above-mentioned cellulose / MXene composite film is placed in a 50°C oven for drying; the above-mentioned step is repeated 11 times on the other side of the cellulose film, and the mass change of the cellulose / MXene composite film is recorded; the graphene oxide aqueous dispersion is evenly sprayed on both sides of the cellulose / MXene composite film and dried to obtain a cellulose / MXene / graphene oxide composite film.
[0102] 6 parts by mass of toluene diisocyanate, 48 parts by mass of acetonitrile and 16 parts by mass of methyl hexanoate were added to a beaker and stirred evenly by magnetic force to obtain a chemical crosslinking solution. The intermediate product of cellulose / MXene / graphene oxide composite film was immersed in a beaker containing the above chemical crosslinking solution and the beaker was sealed with a sealing film; then the beaker was placed in an oven at a temperature of 70°C and reacted for 2 hours. Finally, the cellulose / MXene / graphene oxide composite film was taken out with tweezers and rinsed with acetone 2-3 times to effectively remove the excess chemical crosslinking liquid attached to the surface. The washed cellulose / MXene / graphene oxide composite film was placed in a 50°C oven and dried for 8 hours to obtain a graphene oxide-assisted multi-crosslinked MXene composite film.
[0103] The test results of the photothermal conversion effect and electrothermal conversion effect of the graphene oxide-assisted multi-crosslinked MXene composite film are shown in Figures 1 and 2. Figure 8 , 9 As shown. When the optical power density is 50mW / cm 2 , 100mW / cm 2 and 150mW / cm 2 When the input DC voltage is 0.5V, 1V, 1.5V, 2V and 2.5V, the surface saturation temperature of the graphene oxide-assisted multi-crosslinked MXene composite film can reach 43°C, 69°C and 94°C respectively. When the input DC voltage is 0.5V, 1V, 1.5V, 2V and 2.5V, the surface saturation temperature of the graphene oxide-assisted multi-crosslinked MXene composite film can reach 31°C, 48°C, 60°C, 87°C and 112°C respectively.
[0104] Combined with the above examples, it can be seen that the graphene oxide-assisted multi-crosslinked MXene composite film provided by the present invention has excellent mechanical strength, excellent electrical conductivity, electromagnetic shielding performance, photothermal / electrical heat conversion performance, antibacterial properties, etc. The preparation method of the present invention is simple and efficient, easy to achieve large-scale production, and has broad application prospects.
[0105] The above description is only a preferred embodiment of the present invention and is not intended to limit the present invention. For those skilled in the art, the present invention may have various modifications and variations. Any modification, equivalent replacement, improvement, etc. made within the spirit and principle of the present invention shall be included in the protection scope of the present invention.
Claims
1. A graphene oxide-assisted multi-crosslinked MXene composite film, characterized in that: Its preparation method is: Methylimidazole, 2-chloroacrylonitrile and water are uniformly mixed in a mass ratio of 1-10:2-20:100-250 to prepare an ionic liquid; Dissolving cellulose pulp in an ionic liquid under water bath conditions to obtain a clarified mixed solution, wherein the concentration of cellulose pulp in the mixed solution is 5-20 g / L; extruding the mixed solution into a coagulation bath for coagulation to obtain a large-area cellulose film; The MXene aqueous dispersion was evenly sprayed on both sides of the cellulose film and dried to obtain a cellulose / MXene composite film. Then, the graphene oxide aqueous dispersion was evenly sprayed on both sides of the cellulose / MXene composite film and dried to obtain a cellulose / MXene / graphene oxide composite film. The amount of MXene attached to the composite film was 0.5-10 mg / cm 2 , the amount of graphene oxide attached is 0.1-2 mg / cm 2 ; The cellulose / MXene / graphene oxide composite film is immersed in a chemical cross-linking solution to react, thereby obtaining a graphene oxide-assisted multi-cross-linked MXene composite film; The chemical cross-linking solution is a mixture of a cross-linking agent, acetonitrile and methyl hexanoate, wherein the volume ratio of the cross-linking agent, acetonitrile and methyl hexanoate is 0.5-5:2-30:1-20; The preparation method of the MXene aqueous dispersion is as follows: Ti3AlC2 MAX powder is added to a mixed solution of LiF and concentrated hydrochloric acid in batches for etching, and after etching, the MXene is washed, shaken and layered, and the obtained MXene is added to water and dispersed evenly to obtain the MXene aqueous dispersion; In the mixed solution of LiF and concentrated hydrochloric acid, the mass ratio of LiF to concentrated hydrochloric acid is 3-6:40-60, and the concentration of concentrated hydrochloric acid is 5-8 mol / L.
2. The graphene oxide-assisted multi-crosslinked MXene composite film according to claim 1, characterized in that: The water bath conditions are as follows: the water bath heating temperature is 55-125° C., and the water bath heating time is 0.2-2.5 h.
3. The graphene oxide-assisted multi-crosslinked MXene composite film according to claim 1, characterized in that: The mixed liquid is extruded into the coagulation bath by using an extrusion nozzle, and the width of the extrusion nozzle is selected from one of 1.65 mm, 1.55 mm, 1.36 mm, 1.2 mm, 1.12 mm, 0.84 mm, 0.7 mm, 0.6 mm, 0.51 mm, 0.41 mm, 0.34 mm, 0.3 mm, 0.26 mm, 0.24 mm, 0.21 mm, 0.16 mm, 0.11 mm or 0.06 mm.
4. The graphene oxide-assisted multi-crosslinked MXene composite film according to claim 1, characterized in that: The preparation method of the graphene oxide aqueous dispersion is as follows: dissolving sodium nitrate in concentrated sulfuric acid to obtain a uniform and clear mixed solution; Add graphite powder to the uniform clear mixed solution, cool it in an ice water bath, slowly add potassium permanganate under stirring, stir and react for 5-15 minutes, turn off the agitator, add deionized water to the reaction solution, wait until the temperature of the mixed solution is 65-75° C., add hydrogen peroxide, stir and react for 8-12 hours to obtain a product, wash the product, and evenly disperse it in water to obtain an aqueous dispersion of graphene oxide; Wherein, the mass ratio of the sodium nitrate, concentrated sulfuric acid, graphite powder, potassium permanganate, deionized water and hydrogen peroxide is 0.2-5.0:100-500:0.5-10:10-60:50-500:5-50.
5. The graphene oxide-assisted multi-crosslinked MXene composite film according to claim 1, characterized in that: The crosslinking agent is selected from one or a combination of at least two of hexamethylene diisocyanate, methylene diphenyl isocyanate, polymethylene polyphenyl isocyanate, toluene diisocyanate or isophorone diisocyanate.
6. The graphene oxide-assisted multi-crosslinked MXene composite film according to claim 1, characterized in that: The temperature for chemical cross-linking of the cellulose / MXene / graphene oxide composite film is 65-75° C., and the time for chemical cross-linking is 1.5-2.5 h. During the chemical cross-linking, the reaction container is sealed.
7. The graphene oxide-assisted multi-crosslinked MXene composite film according to claim 1, characterized in that: The concentration of MXene aqueous dispersion is 0.05-1 wt%.
8. The graphene oxide-assisted multi-crosslinked MXene composite film according to claim 1, characterized in that: The concentration of the graphene oxide aqueous dispersion is 0.5-2wt%.
9. The graphene oxide-assisted multi-crosslinked MXene composite film according to any one of claims 1 to 8, characterized in that: The graphene oxide-assisted multi-crosslinked MXene composite film is used in the preparation of electromagnetic shielding, photothermal conversion, electrothermal conversion, thermal conductive materials, sensing materials, electrode materials, biomedical materials, antibacterial materials, supporting materials or wearable flexible electronics.
